Comments on "A Feedback Min-Max MPC Algorithm for LPV Systems Subject to Bounded Rates of Change of Parameters - Ding, B; Huang, B (IEEE transactions on automatic control, 2007)
The commenters point out a major problem with the initialization stage in the technique in the above article by Casavola et al. (see ibid. vol. 47, no. 7, p. 1147-53, 2002)